Aesthetics Considerations for Short and Medium Span Bridges. Issue 4 (2nd October 2021) - Di Bernardo, Salvatore
Abstract: Good bridge designers strive to balance their desire to build structures that serve their community, blend with the surrounding environment and are attractive to users, with financial and other project constraints. For long span bridges, commonly adopted types achieve good aesthetics just through the expression of a suitable, effective structural form. More than a century of achievements and advancements in the design of suspension, cable-stayed bridges, tied arches, trusses and other types of long span bridges do offer an array of possible solutions that, if developed with the right sensitivity and good attention to details, can bring lasting aesthetic value to the built environment. Although a "Form follows Function" approach does not always translate into good bridge aesthetics, that approach can be more challenging for short and medium span bridges, for which utilitarian structural schemes are more commonly adopted. The development of conceptual studies, good structural design and attention to detailing can achieve aesthetic results for these bridge types while meeting project financial constraints through a strong partnership with owners and the right attention to the needs of the community and the surrounding environment. The Vitruvius concept from "De Architectura" of 2050 years ago— a structure must exhibit the three qualities of firmitas, utilitas, venustas— still provides a good framework to develop simple criteria and aesthetics guidelines for bridge designers. This paper presents a range of examples, from concept studies to built projects, to highlight current challenges and possible accomplishments in the aesthetic design of highway and pedestrian bridges of short and medium span. The projects presented in this paper aim to highlight the challenges faced by designers when looking for possible solutions rather than to provide guidelines or describe accomplishments. The projects are all located in the United States and directly involved the author as part of the design.